Komunikacja między generacjami w perspektywie stylistycznej - Kita, Małgorzata (Stylistyka, 2006)
The author is interested in verbal communication problems between generations - the young and the old. The opposition US vs. THEM is reflected in language and its commu[1]nicative use, deepening the distance between the generations. An exclusion of children and youth typical for previous centuries is no longer true. It was replaced by a progressive cultural marginalization of old age people. The differences between the language of the young and the old are manifested on the lexical, phraseological and stylistic levels. Having enumerated the language, stylistic and communicative problems of the theoretical and methodological nature, the author presents three possibilities of inter-generation communication: (1) Each of the interactants maintains one’s own way of speaking and then the communication becomes more difficult or even blocked - confrontation style. (2) Both parties present a mutual compromise tendencies if the aim of the communication act is a mutual understanding - consensual style. (3) The interactants adopt their interlocuto[1]r’s style - adoptive style (chameleon style).